2013
DOI: 10.1016/j.jchromb.2013.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Purification of hepatitis B surface antigen virus-like particles from recombinant Pichia pastoris and in vivo analysis of their immunogenic properties

Abstract: Following earlier studies on high-level intracellular production of hepatitis B surface antigen (HBsAg) using recombinant Pichia pastoris, we present here in detail an enhanced method for the purification of recombinant HBsAg virus-like particles (VLPs). We have screened various detergents for their ability to promote the solubilization of recombinant intracellular HBsAg. In addition, we have analyzed the effect of cell disruption and extraction regarding their impact on the release of HBsAg. Our results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…It shows low viscosity morphology, allowing easy, large-scale, high-cell-density growth in fermenters using inexpensive substrates. Furthermore, this fungus supports broad ranges of pH (4.5-7.0) and temperature (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) C) for growth. A C1 genetic toolbox is available, and the 3eight megabase pair genome has been sequenced, enabling the development of various gene expression strategies.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It shows low viscosity morphology, allowing easy, large-scale, high-cell-density growth in fermenters using inexpensive substrates. Furthermore, this fungus supports broad ranges of pH (4.5-7.0) and temperature (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) C) for growth. A C1 genetic toolbox is available, and the 3eight megabase pair genome has been sequenced, enabling the development of various gene expression strategies.…”
mentioning
confidence: 71%
“…In 2002, P. pastoris was approved in 2002 by the World Health Organization (WHO) for the production of an HBV vaccine biosimilar by Shantha Biotechnologies (a Sanofi company), and this biosimilar has recently been shown to be potentially more effective than vaccines produced in S. cerevisiae in particular patient groups. 33,34 Hyper-mannosylation, a well-known limitation of conventional yeast systems, is weaker in P. pastoris, which has been engineered to produce human-like glycosylation of recombinant proteins by knocking out 4 glycosylationassociated genes and introducing more than 14 heterologous genes. 35,36 In 2004, this technique resulted in the development of Glycoswitch Ò from Merck, a technology allowing for uniform Man5 N-glycosylation and development of a set of vectors to express glycan-modifying enzymes in yeast strains not limited to P. pastoris.…”
Section: Yeast: Lessons Learned From Antiquitymentioning
confidence: 99%
“…The first VLP-like structures appeared after elution of proteins bound to colloidal silica ( Figure 1D). Binding of HBsAg to colloidal silica (Aerosil-380) in clarified PEG extracts at neutral pH through hydrophobic adsorption represents an important step during purification as the elution of bound proteins from colloidal silica already leads to a HBsAg preparation with a purity of 60-70% [37]. An electron microscopic investigation of this eluate revealed that the size of these irregular VLP-like structures were in the range of HBsAg VLPs but clearly neither uniform in size nor in shape ( Figure 1D).…”
Section: Monitoring the Assembly Of Hbsag Vlps During The Purificatiomentioning
confidence: 99%
“…However, the size-exclusion chromatography step removed remaining host cell proteins as the HBsAg VLPs elute with the void volume and host cell contaminants elute afterwards [37].…”
Section: Stability Of Hbsag Vlps In Buffers and Solutions Employed Dumentioning
confidence: 99%
See 1 more Smart Citation